Care of diabetes in children and adolescents: controversies, changes, and consensus. Issue 9982 (23rd May 2015) - Cameron, Fergus J; Wherrett, Diane K
Summary: Diabetes is one of the most common chronic medical disorders in children. The management of diabetes remains a substantial burden on children with diabetes and their families, despite improvements in treatment and rates of morbidity and mortality. Although most children with diabetes have type 1 diabetes, the increasing recognition of type 2 diabetes and genetic forms of diabetes in the paediatric population has important treatment implications. Diabetes therapy focuses strongly on targets for good metabolic control to reduce the risk of long-term complications. A parallel goal is to minimise short-term complications of hypoglycaemia and diabetic ketoacidosis. Technology offers opportunity for improvement in care, but has not yet fully lived up to its potential. New insights into the pathogenesis of diabetes and the development of new therapies have led to clinical trials aimed at the prevention of diabetes.